Utilizing discussion boards for test questions: opportunities for students' mathematical creativity and uniqueness. Issue 3 (16th March 2022) - Savić, Miloš
Abstract : Taking the challenges presented by shifting to online instruction mid-semester due to the Covid-19 global pandemic, I tried to utilize prompts on discussion boards as test questions. The prompts for these questions were to create a triple integral satisfying certain conditions, and when a person posted their integral, no one else could use the same function or bounds. What occurred was a dream to me as an educator – I got to see students being creative, collaborative, and thoughtful, while I enjoyed grading and seeing their uniqueness shine. In this article, I detail the integral prompt and another recent prompt for vectors that led to a merger between my teaching beliefs and actions. I also share about the multiple benefits for instructors, including seeing mathematically clever solutions, and students, including reducing test anxiety and reverse-engineering mathematics problems.